Senam Lansia dan Cek Kesehatan Gratis dalam Mewujudkan Lansia Sehat, Mandiri, dan Produktif di Desa Tambakan, Kecamatan Gandusari, Kabupaten Blitar - Yusvidha Ernata; Shinta Masitho Windriyani; Yuskhil Mushofi; Winarno Winarno; Ahmad Junaidi (Lembaga Pengembangan Kinerja Dosen, 2026)
Old age is a stage in the human life cycle where the body undergoes a decline in physiological functions, including a decrease in muscle strength, organ function, balance, and metabolism. To maintain body functions, it is necessary to keep moving, one way is through elderly exercise adjusted to the characteristics of old age, accompanied by regular health check-ups. The lack of knowledge among residents regarding elderly health is the main reason for this activity. Simple health checks include measuring blood pressure, blood glucose, and body weight. A community service program titled